Innovaciones metodológicas en el estudio de nuevos fenómenos sociales: masificación de los feminismos y transformaciones académicas (2022)
The objective of this paper is to reflect on methodological and academic innovations produced in recent years in Argentina within the framework of the massification of feminist struggles. The article begins by reconstructing epistemological shifts produced in the international field in recent decades with the expansion of feminisms and the admittance of queer theory in the academia. Second, it outlines methodological possibilities that have emerged from positions in line with these shifts. Finally, it exposes the transformations that have occurred in Argentina with the implosion of feminisms since 2015, which has permeated the production of knowledge and generated openings in the rules for writing research papers and in their methodological designs. At this point, the paper focuses on the changes introduced in the Faculty of Social Sciences of the Universidad de Buenos Aires, which has renowned trajectory in working with feminist issues within the Argentine university system. The article is framed in a qualitative methodology and concludes that the feminisms of the last decades, strengthened in recent years, have made visible conservative aspects of our fields of knowledge production and have shaped changes that need to be deepened.